Peptide selectivity discriminates NK cells from KIR2DL2‐ and KIR2DL3‐positive individuals. Issue 2 (29th November 2014) - Cassidy, Sorcha; Mukherjee, Sayak; Myint, Thet Mon; Mbiribindi, Berenice; North, Helen; Traherne, James; Mulder, Arend; Claas, Frans HJ; Purbhoo, Marco A; Das, Jayajit; Khakoo, Salim I
<x xml:space="preserve">Abstract</x> Natural killer cells are controlled by peptide selective inhibitory receptors for MHC class I, including the killer cell immunoglobulin‐like receptors (KIRs). Despite having similar ligands, KIR2DL2 and KIR2DL3 confer different levels of protection to infectious disease. To investigate how changes in peptide repertoire may differentially affect NK cell reactivity, NK cells from KIR2DL2 and KIR2DL3 homozygous donors were tested for activity against different combinations of strong inhibitory (VAPWNSFAL), weak inhibitory (VAPWNSRAL), and antagonist peptide (VAPWNSDAL). KIR2DL3‐positive NK cells were more sensitive to changes in the peptide content of MHC class I than KIR2DL2‐positive NK cells. These differences were observed for the weakly inhibitory peptide VAPWNSRAL in single peptide and double peptide experiments (p < 0.01 and p < 0.03, respectively). More significant differences were observed in experiments using all three peptides (p < 0.0001). Mathematical modeling of the experimental data demonstrated that VAPWNSRAL was dominant over VAPWNSFAL in distinguishing KIR2DL3‐ from KIR2DL2‐positive donors. Donors with different KIR genotypes have different responses to changes in the peptide bound by MHC class I. Differences in the response to the peptide content of MHC class I may be one mechanism underlying the protective effects of different KIR genes against infectious disease.